A Convenção Batista Independente de Língua Alemã (CIBILA) e a reprodução cultural do tradicionalismo pentecostal (1989-2009) - Modes, Josemar Valdir (2020)
This thesis analyzed the Convention of German Language Independent Baptist Churches (CIBILA), which manifests itself in a unique cultural space, originating from a cultural region, but which, due to the population mobility of post-modernity, is immersed in constant exchanges, diluting established borders, transforming space into a cultural boundary zone/band. The guiding thesis of the research was: CIBILA, founded in 1989, propagates a specific culture arising from the intertwining of German, Russian and Swedish cultures, with refinements of adaptation to the Brazilian reality, a culture that was a constituent element of the Convention and which has already it was manifested by the founding churches even in the period when the Convention did not officially exist, but it was present through the integration of churches with similar practices, perpetuating itself in the churches that make up the Convention today and which was called Pentecostal traditionalism. For this analysis, a study was made of German-Russian immigrants who arrived in northwestern Rio Grande do Sul and established the first communities, which fostered CIBILA as well as serving as an experiment for conventional practice. The churches that make up the conventional body are currently located in the states of Rio Grande do Sul, Santa Catarina, Paraná and Mato Grosso. For a hegemonic discourse amidst so many exchanges and to maintain this vectorized culture, CIBILA used a press vehicle, the Newsletter, founded in 1989, capable of disseminating and consolidating the unique culture of these communities, and which functioned as sounding board of your thoughts. His newspaper was of fundamental importance for the maintenance of links and the propagation of new ways of thinking. The culture propagated by this Convention was named in the work of Pentecostal Traditionalism due to the cultural hybridism experienced and manifested by CIBILA, which has traces of traditional German Baptist theologies, of Swedish Pentecostal theology, adapted to two great moments of social mobilization: migration to Russia and migration to Brazil.